An approach to intercalibrate ecological classification tools using fish in transitional water of the North East Atlantic. (August 2016) - Lepage, Mario; Harrison, Trevor; Breine, Jan; Cabral, Henrique; Coates, Steve; Galván, Cristina; García, Pilar; Jager, Zwanette; Kelly, Fiona; Mosch, Eva Christine; Pasquaud, Stephanie; Scholle, Jörg; et al.
Graphical abstract: Highlights: A simple method for intercalibrating fish assessment tools is proposed. A common pressure index is used as common intercalibration metric. More than 70% agreements between assessment tools are obtained after intercalibration. It enables the inclusion of a new method in the intercalibration process. Abstract: A simple procedure to harmonise and intercalibrate eight national methods classifying the ecological status using fish in transitional waters of the North East Atlantic is described. These methods were initially intercalibrated and a new method recently developed was added to this exercise. A common human pressure index pre-classified the status of each water body in an independent way. Ecological class boundaries values were established according to the level of anthropogenic pressure using regression analyses. A simulated dataset was used to assess the level of agreement between the fish classification methods. Fleiss' multi-rater kappa analysis indicated that boundary harmonisation was achieved; all classifications fell within one class of each other and class agreement between methods exceeded 70%. The use of a pressure index to establish boundary thresholds provides a practical method of defining and harmonizing the quality classes associated with human pressures, as required by the European Water Framework Directive.